1993
DOI: 10.1093/glycob/3.6.633
|View full text |Cite
|
Sign up to set email alerts
|

Structure--function studies on selectin carbohydrate ligands. Modifications to fucose, sialic acid and sulphate as a sialic acid replacement

Abstract: The selectins are a family of carbohydrate-binding proteins that have been implicated in the initial interaction between leukocytes and the vascular endothelium. The three members of this family will bind to the sialyl-Lewisx epitope [Sia alpha 2-3 Gal beta 1-4 (Fuc alpha 1-3) GlcNAc] and related oligosaccharides. In this report, we examine the molecular details of that recognition using synthesized carbohydrates with specific modifications on the sialyl-Lewisx epitope. E- and L-Selectin require hydroxyl group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
87
1
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(98 citation statements)
references
References 0 publications
9
87
1
1
Order By: Relevance
“…Fourth, the presence of the 3Ј-linked fucose on 6-sulfo,3Ј-sialyl-Le x is essential for Lselectin binding. In accord with this finding is an earlier report that L-selectin binding is abolished by modification of the fucose in the 3Ј-sialyl-Le x sequence by removal of oxygen at position 2, 3, or 5 (18). The presence of the fucose is apparently less critical in the 3Ј-sulfo-Le x sequence as it has been observed that the defucosylated 3Ј-sulfo-Le x tri-and tetrasaccharides are bound by L-selectin, albeit less strongly than the 3Ј-fucosyl analogs (4,5).…”
Section: Discussionsupporting
confidence: 88%
“…Fourth, the presence of the 3Ј-linked fucose on 6-sulfo,3Ј-sialyl-Le x is essential for Lselectin binding. In accord with this finding is an earlier report that L-selectin binding is abolished by modification of the fucose in the 3Ј-sialyl-Le x sequence by removal of oxygen at position 2, 3, or 5 (18). The presence of the fucose is apparently less critical in the 3Ј-sulfo-Le x sequence as it has been observed that the defucosylated 3Ј-sulfo-Le x tri-and tetrasaccharides are bound by L-selectin, albeit less strongly than the 3Ј-fucosyl analogs (4,5).…”
Section: Discussionsupporting
confidence: 88%
“…5). These data are consistent with prior studies on the sensitivity of sialoadhesin and CD22 binding to modifications of the sialic acid residue (6, 33, 46 -48) and contrast with studies on selectins, in which extensive modifications of sialic acids have no effect (12,14,49). In fact, substitution of the entire sialic acid (e.g.…”
Section: Figsupporting
confidence: 91%
“…In certain sialic acid-dependent recognition systems, determinant stringency is low. For example, selectins bind to oligosaccharides bearing truncated sialic acids (12) or appropriately placed anionic groups (sulfates, carboxylic acids) otherwise unrelated to the sialic acid structure (13)(14)(15)(16). In contrast, sialoadhesins appear to have more stringent sialic acid specificities (see "Discussion") (9).…”
mentioning
confidence: 99%
“…Binding of selectins to de-N-acetyl sialyl 6-sulfo Lewis X was also not unexpected because the amino residue at C-5 position is known not to be intimately involved in interaction with selectin; even KDN-Lewis X, which lacks the amino group at C-5, is known to bind to selectins, almost as equally as genuine sialyl Lewis X does (26,27). L-and P-selectins showed preferential binding to sialyl 6-sulfo Lewis X and de-N-acetyl sialyl 6-sulfo Lewis X rather than to classical sialyl Lewis X whereas E-selectin bound better to classical sialyl Lewis X.…”
Section: Resultsmentioning
confidence: 99%